Choice of cooperation model of the logistics department with other departments of an importing company - E. M. Tettsoeva (Управление)
One of the important challenges for importing companies is reducing of the non-productive work time expenditures of the logistics staff, which are created by inefficient order of interaction between the procurement department and the other organizational units. The article describes the basic range of issues that are addressed during the course of the interaction of the procurement logistics division with the other departments of an importing company. The research details the documentation circulating between the business units by dividing it into two indicative groups of the documents - incoming and outgoing - depending on the direction of its flow in the organization in relation to the logistics department. The author emphasizes the importance of the choice of the organizational structure type through which there will be performed the processes of logistics management in the company for better internal communication. The article provides the basic principles that could serve to allocate the internal structural sub-divisions of the logistics department, and also the specific examples of combination of few approaches for certain logistics functions. The special attention is paid to the format for interaction between the staff of different business units and to the main challenges that exist in this area. The research allowed to make some suggestions on addressing the identified problems. Among the measures proposed are spreading of the logistics principles on the activity of all divisions of the company, better distribution of the tasks relating to the generation of material flow parameters between the logistics department and the sales department of an importing company, regulating of business processes in logistics and wider deployment of the information technologies in the business communication.